The genealogy of Yun Ling’s ressentiment in Tan Twan Eng’s The Garden of Evening Mists - Pellano, Seneca Nuñeza (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This reading of Tan Twan Eng’s Garden of Evening Mists (2012) intends to examine the concept of Nietzschean ressentiment contained within the consciousness of the novel’s main character Yun Ling, a war survivor who directs her subdued loathing, against her Japanese former oppressors and towards a Japanese gardener who has lived in Malaysia after the war. Grounding the paper’s analysis on Nietzsche’s On the Genealogy of Morals (GM), this paper aims to represent Yun Ling’s narrative as an interpretation on the evolution of ressentiment as an internalised hatred — tracing the origins of its conception towards its eventual dissipation. Specifically, it explores Nietzschean concepts pertinent to Yun Ling’s narrative such as: 1.) justice as an invention of the powerless; 2.) forgetting as a positive form of repression; 3.) memory as a painful continuation of a promise; and 4.) the body as the site of history. Moreover, these aphoristic ideas from Nietzsche are contextualised to explicate aspects relevant to Yun Ling’s character such as her Malaysian Chinese identity, the Japanese occupation of Malaya, and healing through Japanese aesthetics.